Analysis Of Factors Associated With Gout Arthritis At The Bantal Health Centre, Muko-Muko Regency - Candra, Heri; Fauzi, Yusran; Darmawansyah, Darmawansyah (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Gouty arthritis is an inflammation of the joints. WHO data in 2022, shows the prevalence of gouty arthritis in the world is 41.2%. Riskesdas data on the prevalence of gouty arthritis in Indonesia has increased by 11.9%. Cases of gouty arthritis from the Mukomuko Health Office data in 2022 were 248 cases. The aim of the study was to determine the factors associated with the incidence of Gout Arthritis at the Bantal Health Centre, Mukomuko Regency. This research is a quantitative research using cross sectional study design. The number of samples in the study were 78 respondents. The sampling technique used accidental sampling. The analysis used was univariate and bivariate analysis with chi-square test. The results showed that almost half of the respondents suffered from Gouty Arthritis by 38.5%, most of the respondents had an age < 60 years as many as 57 respondents (73.1%), most of the respondents were female as many as 56 respondents (71.8%), almost all of the respondents had BMI ≤ 25 as many as 65 respondents (83.3%), there was a significant relationship between age (p = 0.000), gender (p = 0.000) with the incidence of gouty arthritis, there was no significant relationship between nutritional status and the incidence of gouty arthritis at Puskesmas Bantal, Mukomuko Regency (p = 0.118). It is hoped that further research can look at other risk factors using a more in-depth research design and analysis.